2020
DOI: 10.1177/0004867420968886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evening light exposure on sleep in bipolar disorder: A longitudinal analysis for repeated measures in the APPLE cohort

Abstract: Objective: Sleep disturbance, a core feature of bipolar disorder, is associated with residual mood symptoms, mood episode recurrence and suicide ideation. We investigated the effect of evening light exposure on sleep in patients with bipolar disorder. Methods: In this longitudinal analysis, we measured the sleep parameters of 207 outpatients with bipolar disorder using actigraphy at their homes for seven consecutive nights. We measured the white-light illuminance and the irradiance of each wavelength during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
5
3
Order By: Relevance
“…5 LAN exposure is closely linked to the pathophysiological processes underlying bipolar disorder, such as alterations in mood symptoms, circadian rhythm, and sleep quality as well as obesity. [6][7][8][9] Our cross-sectional study demonstrated that increased LAN exposure in real-life situations (≥3 lux) is associated with an increased occurrence of manic symptoms in patients with bipolar disorder. 6 Furthermore, dark therapy, in which patients spend the night in a completely dark room (<5 lux), has been found to be beneficial in manic patients.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…5 LAN exposure is closely linked to the pathophysiological processes underlying bipolar disorder, such as alterations in mood symptoms, circadian rhythm, and sleep quality as well as obesity. [6][7][8][9] Our cross-sectional study demonstrated that increased LAN exposure in real-life situations (≥3 lux) is associated with an increased occurrence of manic symptoms in patients with bipolar disorder. 6 Furthermore, dark therapy, in which patients spend the night in a completely dark room (<5 lux), has been found to be beneficial in manic patients.…”
mentioning
confidence: 66%
“…With the widespread use of artificial light in modern society, exposure to light at night (LAN) is common in daily life 5 . LAN exposure is closely linked to the pathophysiological processes underlying bipolar disorder, such as alterations in mood symptoms, circadian rhythm, and sleep quality as well as obesity 6‐9 . Our cross‐sectional study demonstrated that increased LAN exposure in real‐life situations (≥3 lux) is associated with an increased occurrence of manic symptoms in patients with bipolar disorder 6 .…”
Section: Introductionmentioning
confidence: 83%
“…In elderly individuals exposed to light at night under home setting conditions, similar effects were observed on sleep (i.e., increase of the latency to initiate sleep) [ 66 ]. Furthermore, in subjects suffering from bipolar disorder, a significant correlation between the intensity of light exposure at night and the presence of manic symptoms and altered sleep (e.g., latency to initiate sleep and episodes of waking during sleep) was reported [ 67 , 68 ].…”
Section: Nighttime Light Effects On Sleep and Circadian Biology Of Diurnal Mammalsmentioning
confidence: 99%
“…There have been two studies in Japan, one in older adults (Obayashi et al, 2014) and one in patients with bipolar disorder (Esaki et al, 2021), that examined night‐to‐night white light exposure (lux) in the 4‐hr period preceding sleep. In the study of older adults, they examined only light exposure during 4 hr preceding sleep in relation to sleep latency, and found greater evening light exposure was associated with increased sleep‐onset latency (Obayashi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of older adults, they examined only light exposure during 4 hr preceding sleep in relation to sleep latency, and found greater evening light exposure was associated with increased sleep‐onset latency (Obayashi et al, 2014). In the study of patients with bipolar disorder, greater light exposure was related to lower sleep efficiency, increased sleep‐onset latency and more time spent awake during the night (Esaki et al, 2021). These studies indicate that greater light exposure in the 4 hr preceding sleep was associated with poorer sleep health.…”
Section: Introductionmentioning
confidence: 99%